2019
DOI: 10.1111/lam.13109
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative method to assess the role of indoor air decontamination to simultaneously reduce contamination of environmental surfaces: testing with vegetative and spore-forming bacteria

Abstract: Indoor air can spread pathogens, which can be removed/inactivated by a variety of means in healthcare and other settings. We quantitatively assessed if air decontamination could also simultaneously reduce environmental surface contamination in the same setting. Two types of vegetative bacteria (Staphylococcus aureus and Acinetobacter baumannii), and a bacterial spore‐former (Geobacillus stearothermophilus) were tested as representative airborne bacteria. They were separately aerosolized with a Collison nebuliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 16 publications
(26 reference statements)
0
7
1
Order By: Relevance
“…10,11 Our results showed a positive correlation between bacterial CFUs in the air and on the floors and HCSs, both in the discharge outlet and at the centre of rooms, probably due to the deposit of the first over the second, which corroborates that there is a continuous interaction between the air and surfaces. 16,18,35 In this study, CFUs of bacteria on surfaces were not found in 44% of floor samples and in 63.6% of HCSs. When CFUs were present, 75% of floors had less than 12 or 39 CFU/100 cm 2 , and less than 2 or 6 CFU/100 cm 2 of bacteria on HCSs (with and without a terminal HEPA filter, respectively).…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…10,11 Our results showed a positive correlation between bacterial CFUs in the air and on the floors and HCSs, both in the discharge outlet and at the centre of rooms, probably due to the deposit of the first over the second, which corroborates that there is a continuous interaction between the air and surfaces. 16,18,35 In this study, CFUs of bacteria on surfaces were not found in 44% of floor samples and in 63.6% of HCSs. When CFUs were present, 75% of floors had less than 12 or 39 CFU/100 cm 2 , and less than 2 or 6 CFU/100 cm 2 of bacteria on HCSs (with and without a terminal HEPA filter, respectively).…”
Section: Discussioncontrasting
confidence: 53%
“…A continuous interaction between air and surfaces exists, 16,17 as particles are deposited on surfaces and subsequently resuspended. 18 Bacterial survival in the air is correlated to indoor environment and design parameters (air filter, the direction of airflow, air pressure, air changes per hour (ACH), humidity, temperature).…”
Section: Introductionmentioning
confidence: 99%
“…Some commercially available air filters have been tested within experimental chambers, designed to replicate bioaerosols in an indoor setting. One study conducted in Canada in 2018 replicated specific bioaerosols to determine the effectiveness of a filter in reducing surface contamination [ 20 ]. The experimentally contaminated air was filtered using a portable device which combined HEPA filtration and UV light.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have assessed the combination of UV-C and other disinfection methods. When HEPA filtration was combined with UV, the system reduced more than 99.9% of viable airborne Klebsiella pneumoniae, Acinetobacter baumannii, and S. aureus after 45 min of operation in an aerobiology chamber [59,60]. An ultraviolet photocatalytic oxidation (UV-PCO) scrubber showed 3.5 to 5.3 log reduction of airborne Enterococcus faecalis with one UV lamp operating (average UV irradiation 6595 µW/cm 2 at a contact time of 1 s) and a 7.5 log reduction with two lamps operating, although it should be noted that the irradiation varied markedly depending on proximity.…”
Section: Uv-c (Wavelength 200-280 Nm)mentioning
confidence: 99%